Efektivitas Model Project Based Learning (PjBL) Berbasis Proyek Daur Ulang dalam Meningkatkan Pemahaman Konsep IPAS Siswa Kelas V - Inni Rahmieni Nabila; Mahmud My; Paujan Azim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of students’ conceptual understanding in Natural and Social Sciences (IPAS) among fifth-grade students at MIS Al-Mukhlisin Alam Barajo, Jambi City, particularly on the topic of water pollution. This issue was caused by teacher-centered instruction, which limited students’ opportunities to engage in meaningful and contextual learning experiences. This study aimed to examine the effect of implementing the Project Based Learning (PjBL) model through a recycling project on students’ conceptual understanding of IPAS. A quantitative approach was employed using a pre-experimental One Group Pretest–Posttest Design. The study involved 33 students selected through a saturated sampling technique. Data were collected using tests, observation, interviews, and documentation, and analyzed using the Shapiro-Wilk normality test, Paired Sample t-Test, and N-Gain test with SPSS software. The results showed that the mean pretest score of 60.88 increased to 86.30 in the posttest, with an improvement of 25.42 points. The Paired Sample t-Test revealed a significance value of < 0.001 < 0.05, indicating a significant difference between pretest and posttest results. Furthermore, the N-Gain score of 0.6758 was categorized as moderate with a fairly effective improvement level. Therefore, it can be concluded that the implementation of the Project Based Learning (PjBL) model through a recycling project has a significant and fairly effective impact on improving students’ conceptual understanding of IPAS in grade V MIS Al-Mukhlisin Alam Barajo, Jambi City.